THE CONFLICTING VALUES AMONG GENERATIONS IN D.H.LAWRENCE’S THE VIRGIN AND THE GIPSY - Suryani Kurniawi Kahi Leba Kapoe (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This research aims at studying the conservative versus the modern characters in Lawrence’s The Virgin and The Gipsy. The research is a qualitative and library research. The data gathered are especially taken from the main source which is the novel itself. Besides that, to support the study the writer gets some data from books and internet and the objective theory of literature. The study finds out that in Lawrence’s, there are some different views between the young generation and the old generation. The definition and the essence of the study presumed by the writer are based on the character of the two generations in an era. The old generation is a type of person who tends to control and dominate the young. They have an absolute power. On the other hand, the young wants to be free and they have different way of views and appreciate life. Keywords: dominate, control, free, power.